Temperatures of Entering Magma, Formation and Dimensions of Magma Chambers of Volcanoes - Fedotov S.A. (F. Giannini, 1982)
A mechanism, of formation of magma chambers that feed volcanoes is discussed. Heat conditions and dimensions of magma chambers which have existed for more than several thousand years may become stable. The approximate equations of heat balance of these chambers are derived by calculating the temperature T1 of the magma entering chambers and the radii a of chambers. Calculations show that the radius of the shallow "peripheral" chambers of the Avachinsky volcano is less than 3-3.5 km. Possible maximum radii of "peripheral" magma chambers were estimated for the Kamchatkan volcanoes of medial size. The temperature difference in their chambers may reach 100-200 "C. This method can be applied to the calculations of "roots" of central-type volcanoes.
Keywords: 38.37.25 Вулканология